Review by the official opponent of Doctoral (Law) thesis (major 12.00.08 - criminal law and criminology; criminal-execution law): “Theoretical and applied issues of counteracting the criminal exploitation of a human (criminological research)” by V. I. Kovalenko - S. F. Milyukov (Russian Journal of Economics and Law, 2018)
Objective: to comprehensively analyze the Doctoral dissertation “Theoretical and applied issues of counteracting the criminal exploitation of a human (criminological research)” by V.I. Kovalenko, successfully defended in 2017 at Dissertation Council of All-Russia Scientific-research Institute of the Russian Ministry of Internal Affairs.Methods: dialectical approach to the cognition of social phenomena, enabling to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-legal, comparative-legal, etc.Results: the author investigates the concept of the system of counteracting the criminal exploitation of humans, its structure, the main trends of criminal exploitation of humans and the possibility of optimal response of the state and the society to this phenomenon. The work focuses on the unconditional benefits of the study, primarily for criminologists studying the problems of combating criminal exploitation of humans. A number of the dissertation provisions are critically analyzed. The author makes the conclusion about the need for criminological assessment of the exploitation of humans without violence and suggests improving the proposals on forming the Conception of prevention of humans’ criminal exploitation. The reviewer expressed his position on the basic concepts and categories used in the dissertation research, such as “personal freedom”, “conceptual bases”, “criminal exploitation”, and reveals their vision in relation to the conducted research.Scientific novelty: the author gives a legal assessment of Doctoral dissertation “Theoretical and applied issues of counteracting the criminal exploitation of a human (criminological research)” by V.I. Kovalenko, reveals its main advantages and the provisions requiring additional scientific study or argumentation.Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activity when considering issues related to theoretical and applied problems of combating criminal exploitation of humans.